A python script for longitudinally measuring the duration of vacant land uses. Issue 1 (2nd January 2022) - Newman, Galen; Kim, Youjung; Kim, Gunwoo; Lee, Ryun Jung; Gu, Donghwan; Forghanparast, Kaveh; Goldberg, Daniel
ABSTRACT: Populating and depopulating cities have some degree of underutilised land. The duration of vacancy, or length of time a property remains unused, more strongly influences urban decline than the amount of vacant land. Assessment of the duration of vacancy is seldom conducted, due to a lack of linking longitudinal data. This research creates and applies a Python script to track the duration of vacancy in Minneapolis, MN, U.S.A, to create a tool that can be utilised by cities with vacant land inventories. The tool can be used globally to prioritise treatment areas for urban regeneration plans.